A Review on Advanced Encryption Standard – (AES) - Karki, Ajit (International Journal of Computer Sciences and Engineering, 2025)
Cryptography is the study of mathematical techniques related to aspects of information security such as confidentiality, data integrity, entity authentication and data origin authentication. In data and telecommunications, cryptography is necessary when communicating over any unreliable medium, which includes any network particularly the internet. AES encryption is the solution for Data Encryption Standard (DES) aging problem. Rijndanel Symmetric block cipher standard version which can encrypt and decrypt plaintext 128 bits blocks using key with 128-bit, 192-bit, or 256-bit size. The Rijndael cipher has simple structure and suitable to 8-bit and 32-bit processing. The cipher has numbers round of plaintext transformation. Key length determines how many rounds to be executed. The key with 128-bit use 10 rounds, 192-bit use 12 rounds, and 256-bit use 14 rounds. For the AES algorithm, the number of rounds to be performed during the execution of the algorithm uses a round function that is composed of four different byte-oriented transformations: Sub Bytes, Shift Rows, Mix columns and Add Round Key.